Impacto del turismo en indicadores de empleo durante la emergencia sanitaria del cantón Quevedo, año 2021 - Piedra Morán, Alisson Melissa (2021)
The pandemic has not only caused tragic loss of human lives and damage to the health of individuals and communities, but has also had devastating consequences in the world of work. It triggered a growth in unemployment, underemployment and inactivity, loss of income for workers and businesses. The World Travel and Tourism Council, which considers that the health emergency caused by COVID-19 has put at risk 50 million employees in the sector around the world, which is between 12% and 14% of the tourism sector. The coronavirus crisis caused a destabilization of the hotel sector, due to massive cancellations of hotel reservations made by consumers, who are on standby, but continue to maintain the intention to travel if the situation evens out or improves. The city of Quevedo is recognized as one of the most important river ports in the country, however, during the outbreak of the coronavirus (COVID-19) Quevedo has been severely threatened, losing countless citizens every day. Employment became one of the most affected variables. Hundreds of people were left without adequate employment in the strongest months of the pandemic. They have caused a financial downturn, bringing with it discouraging results. It is therefore important to consider strategies to restructure the tourism sector, creating new products and projects for tourists and post-covid consumers, which include new economic and sanitary measures that are focused on domestic tourism.